Freelance [videorecording (DVD)] - Lentz, Jacob, (Screenwriter); Cena, John; Brie, Alison; Raba, Juan Pablo, 1977-; Eve, Alice, 1982-; Csokas, Marton, 1966-; Slater, Christian (Relativity Media LLC, 2024)
Ex-special forces operative Mason Pettis is stuck in a dead-end desk job when he reluctantly takes on a freelance gig to provide private security for washed-up journalist Claire Wellington as she interviews the ruthless but impeccably dressed dictator, Juan Venegas. When a military coup breaks out just as she's about to get the scoop of a lifetime, the unlikely trio must figure out how to survive the jungle AND each other to make it out alive!